Pengaruh Kuliah Kerja Nyata Mahasiswa Fakultas Ekonomi Universitas Samudra terhadap Pengembangan Kompetensi Sumber Daya Manusia - Syardiansah Syardiansah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
This study was conducted to determine the effect of real work on the development of human resource competencies (students) at the Faculty of Economics at the University of Samudra who had attended real work classes in 2018. The number of respondents in this study was 150 students from the Management Study Program, Economics Level IV Development and Accounting Economics that has attended real work classes in 2018. Using the Slovin formula, there are 60 students as a sample. The data in this study were obtained from the results of distributing questionnaires to students as many as 60 questionnaires which were all returned without defects. From the results of data analysis, it was found that there were positive and significant influences on KKN on improving human resource competencies, namely personality competencies and social competencies. Where the coefficient of determination (R2) personality competence is 21.2% while the remaining 78.8% is influenced by other variables not examined in this study. The coefficient of determination (R2) of social competence is 21.4% while the remaining 78.6% is influenced by other variables not examined in this study